Advanced Fuel Property Data Platform: Overview and Potential Applications - Blakey, Simon; Rauch, Bastian; Oldani, Anna; Lee, Tonghun (Frontiers in Energy Research, 2022)
This report outlines the establishment of distributed databases for management and integration of current and future aviation fuels. Aviation fuel property and performance data has been gathered for many years in public and company specific fuel surveys. These surveys are suitable for use as overall quality control information and for monitoring changes and trends in the fuels in used for flight. In recent years, significant data has been generated for alternative fuels as part of the due diligence of their approval for use through ASTM D4054, including those outside of the specification. Recently, this data, along with fundamental chemistry data has led to the creation of the Fast Track route for fuels approval when the fuel is constrained to a necessarily narrowly defined composition. The data behind these developments are often stored in a disparate, unindexed way, resulting in their underutilisation for a range of research, engineering design, specification, and in service quality control applications. To make the best use of this data, we present a scalable, Json based format for the storing of fuels data. This concept has been proposed by the Horizon 2020 Jet Fuel SCREENing and Optimization (JETSCREEN) project in conjunction with the Center of Excellence for Alternative Jet Fuels and Environment (ASCENT) programme. We have worked collaboratively to develop a joint database which currently contains data from around 30,000 conventional and 400 alternative fuels/fuel blends from a range of European and United States of America (U.S.) lead research programmes and data sources. This database can be used for a variety of purposes, both in conjunction with, or in isolation of commercially sensitive data with a greater degree of restriction. We present a number of test cases for how we see this model for data storage could be used for the benefit of all. We invite further suggestions as to how this approach could be used and welcome opportunities to work with the wider fuels community to develop this idea further.